Saving Hong Kong Disappearing Village Heritage - LAU, Man Kwan Julia; CHOW, Kwai Shun Mirage (MAJ - Malaysia Architectural Journal, 2025)
Fu Tei Au Village (FTAV) is located in the northern part of New Territories, a suburban region of Hong Kong (HK). This area is incorporated into the "Northern Metropolis" (NM) initiative, a comprehensive development plan announced by the Government of the Hong Kong Special Administrative Region in 2020. FTAV possesses historical significance, particularly due to its red bricks inscribed with the KCR (Kowloon Canton Railway) lettering, indicative of its past ownership by the Kowloon Canton Railway Brick Company. Additionally, FTAV holds considerable ecological importance, showcasing a rich biodiversity. Notably, it is home to a remarkable habitat of fireflies, exhibiting a striking fluorescent green bioluminescence. However, due to the unfortunate inability to secure further funding from the relevant governmental authorities for ongoing research, there are concerns regarding the potential loss of this unique ecological site amid conservation efforts. Therefore, it is imperative to document and raise awareness about FTAV at this juncture.